Worlds Apart? Unemployment Policy and Politics in Britain and France - Daniel Clegg; Jochen Clasen (Revue Française de Civilisation Britannique)
Unemployment policies in Britain and France during the 1990s are often presented as being very different, and even ‘worlds apart’. The reason is held to be the effect of contrasting social values on the evolution of labour market regulation in the two countries. However, behind the well-known global figures on which this argument usually rests, we can identify a considerably more complex reality. The characterisation of each country’s unemployment policies must also take into consideration more ambiguous variations, which appear to depend as much on the impact of inherited institutional structures as on truly antagonistic values.